2007
DOI: 10.1016/j.virol.2007.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Simian varicella virus reactivation in cynomolgus monkeys

Abstract: SVV infection of primates closely resembles VZV infection of humans. Like VZV, SVV becomes latent in ganglionic neurons. We used this model to study the effect of immunosuppression on varicella reactivation. Cynomolgus monkeys latently infected with SVV were irradiated and treated with tacrolimus and prednisone. Of four latently infected monkeys that were immunosuppressed and subjected to the stress of transportation and isolation, one developed zoster, and three others developed features of subclinical reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 36 publications
1
74
1
Order By: Relevance
“…Reactivation of both VZV (14,24,34) and SVV (23,28,33) is also associated with exposure to ionizing radiation. Moreover, VZV DNA and infectious virus are present in the saliva of astronauts during and shortly after space flight (11,30), and preliminary investigations suggest that ionizing radiation is the major cause of VZV reactivation in astronauts (S. K. Mehta, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation of both VZV (14,24,34) and SVV (23,28,33) is also associated with exposure to ionizing radiation. Moreover, VZV DNA and infectious virus are present in the saliva of astronauts during and shortly after space flight (11,30), and preliminary investigations suggest that ionizing radiation is the major cause of VZV reactivation in astronauts (S. K. Mehta, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…SVV (a deltaherpesvirus strain) isolated from a naturally infected monkey (Erythrocebus patas) was propagated in Vero (African green monkey kidney) cells, and a virus stock was prepared as described previously (9). SVV-seronegative rhesus macaques (monkeys HB62, HI83, HF39, HC44, HA95, II49, and IK10) were inoculated intrabronchially with 10 4 PFU of wild-type SVV (monkeys HB62, HI83, HA95, II49, and IK10) or SVV expressing enhanced green fluorescent protein (SVV-EGFP) (monkeys HF39 and HC44) as described previously (4,10). Earlier, we demonstrated that SVV-EGFP is pathogenic in African green monkeys and that SVV-EGFP is mildly attenuated compared to wild-type SVV (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…All immunosuppressive treatments were performed as described previously (4). Five months after primary infection, monkeys HB62, HI83, HF39, and HC44 were transported by van (2-h round trip) from the Tulane National Primate Research Center in Covington, LA, to the Tulane University Cancer Center in New Orleans, LA, anesthetized, and exposed to a single dose of 200-cGy total body X-irradiation and then started on daily oral treatment with 500 g (80 g/kg of body weight/day) of tacrolimus (Prograf) and 5 mg (2 mg/kg/ day) of prednisone until they were euthanized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, immunization of Erythrocebus patas with VZV can protect the animals from SVV challenge, demonstrating the antigenic relatedness of the two viruses (30). SVV can also reactivate in animals exposed to social/environmental stress such as transportation or introduction of new animals into an existing group (31)(32)(33)(34) as well as in animals subjected to immune system-suppressive treatments (35)(36)(37)(38). Thus, infection of nonhuman primates (NHP) with SVV provides a translational model with which to gain insight into the anti-VZV T cell response.…”
mentioning
confidence: 99%